2013
DOI: 10.1038/ijos.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acrylamide monomer addition to the acrylic denture-base resins on mechanical and physical properties

Abstract: The aim of the study was to evaluate the effect of adding acrylamide monomer (AAm) on the characterization, flexural strength, flexural modulus and thermal degradation temperature of poly(methyl methacrylate) (PMMA) denture-base resins. Specimens (n=10) were fabricated from a conventional heat-activated QC-20 (Qc-) and a microwave heat-activated Acron MC (Ac-) PMMA resins. Powder/liquid ratio followed the manufacturer's instructions for the control groups (Qc-c and Ac-c) and for the copolymer groups, the resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…From the included researches in the systematic review, the modification of MMA was done basically by certain monomers or solutions that can be categorized as fluoromonomers[2627282930] ( n = 5), phosphate monomers[313233] ( n = 3), methacrylic acid monomer[343536373839] ( n = 6), itaconate monomers[404142] ( n = 3), nitromonomers[543444546] ( n = 5), and nonspecific monomers or solutions ( n = 6). Nonspecific monomers include Norbonyl/phenyl methacrylate (NBMA/PHMA),[47] polyhedral oligosilsesquioxane (POSS),[48] methacrylated dendrimer (DD1),[49] 1,3-bis(3-methacryloxypropyl)-1,1,3,3 tetramethyl disiloxane (BMPMS),[50] silver nitrate (AgNO 3 ) solution,[51] and N -acetyl cysteine (NAC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the included researches in the systematic review, the modification of MMA was done basically by certain monomers or solutions that can be categorized as fluoromonomers[2627282930] ( n = 5), phosphate monomers[313233] ( n = 3), methacrylic acid monomer[343536373839] ( n = 6), itaconate monomers[404142] ( n = 3), nitromonomers[543444546] ( n = 5), and nonspecific monomers or solutions ( n = 6). Nonspecific monomers include Norbonyl/phenyl methacrylate (NBMA/PHMA),[47] polyhedral oligosilsesquioxane (POSS),[48] methacrylated dendrimer (DD1),[49] 1,3-bis(3-methacryloxypropyl)-1,1,3,3 tetramethyl disiloxane (BMPMS),[50] silver nitrate (AgNO 3 ) solution,[51] and N -acetyl cysteine (NAC).…”
Section: Resultsmentioning
confidence: 99%
“…The monomers used to substitute with MMA (wt/vol%) were either experimentally synthesized[33424445474951] or purchased. [526272829303234353637383940414346485052] For the specimen preparation, the polymer beads were synthesized by bulk polymerization,[29474950] suspension polymerization,[2627283334] or from the commercially available pre-polymers. The commercially available pre-polymers used were Lucitone 550,[30354345] Lucitone 199,[3132] Paladent 20,[48] Trevalon,[36] Vertex,[3744] DPI,[3839] Ondacryl,[5] Ivoclar Vivadent,[51] Biocryl,[404142] QC-20, Acron MC,[46] and Uniffasttrad.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of a monomer to a polymer is a matter of interest to obtain materials with superior properties that can be used as alternatives to PMMA 4,6,7) . Studies have reported that different monomers had been incorporated into MMA to reinforce PMMA 3,4,6,7,12,19,[23][24][25] . Nonetheless, the results of these studies, though different from each other, failed to create a material superior to PMMA.…”
Section: Discussionmentioning
confidence: 99%
“…A repair gap of 3 mm was used in this study as it decreased the degree of polymerization contraction and also reduced any color difference between the denture base and repair material. [ 8 ] Ayaz and Durkan[ 10 ] observed that mechanical strength of the specimens reached optimum strength after immersing them in water for 1 day–1 week. Hence, the specimens were stored in distilled water at 37°C for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Glass fibers improve the mechanical properties, but their high cost limits their routine clinical use. [ 10 ] Previously, the addition of alumina into PMMA resulted in increased thermal conductivity and hardness. Silane coupling agent can be used for surface modification of filler which improves the surface bonding of filler and resin matrix.…”
Section: Introductionmentioning
confidence: 99%